Pengembangan Media Video Fenomena Predasi Insektivora dalam Pembelajaran Biologi Secara Daring di SMA PGRI 2 Kota Jambi : (Development Of Video Media For Insectivorous Predation Phenomena In Online Biology Learning At SMA PGRI 2 Jambi City) - Risma Hesy Amrulia; Asni Johari; Pinta Murni (BIODIK, 2022)
Learning media in the form of video is a medium that can be used by teachers to be used in learning. Video media contains learning materials that are equipped with pictures and videos that make it easier to understand the material. This study aims to develop learning media in the form of videos, determine the feasibility, responses of teachers, students, and the effectiveness of video media that have been developed to improve learning outcomes. Video media development uses the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. Video media products are validated by media experts and material experts with excellent results. The results of the biology teacher's response as well as small group and large group trials obtained very good results. The results of the effectiveness test using the paired-sample t test showed that there was an effect on the use of video media on the insectivorous predation phenomenon in improving student learning outcomes. Based on the results obtained, it is concluded that the media developed is suitable for use in learning. Key words: Video Media, Online Learning, Insectivorous Predation Phenomen Â  Abstrak. Media pembelajaran berupa video merupakan media yang bisa dipakai oleh guru untuk digunakan dalam pembelajaran. Media Video memuat materi pembelajaran yang dilengkapi dengan gambar serta video yang memudahkan dalam memahami materi. Penelitian ini bertujuan untuk mengembangkan media pembelajaran berupa video, mengetahui kelayakan, respon guru, peserta didik, serta efektivitas media video yang telah dikembangkan dalam meningkatkan hasil belajar. Pengembangan media video menggunakan model ADDIE yang terdiri dari tahap analysis, design, development, implementation dan evaluation. Produk media video divalidasi oleh ahli media dan ahli materi dengan perolehan hasil sangat baik. Hasil respon guru biologi serta ujicoba kelompok kecil dan kelompok besar diperoleh hasil sangat baik. Hasil uji efektivitas menggunakan uji paired sample t test menunjukkan terdapat pengaruh pada penggunaan media video pada materi fenomena predasi insektivora dalam meningkatkan hasil belajar peserta didik. Berdasarkan hasil yang diperoleh maka disimpulkan bahwa media yang dikembangkan layak untuk digunakan dalam pembelajaran. Kata kunci: Media Video, Pembelajaran Daring, Fenomena Predasi Insektivora